On Nearly $α$-Boundedness in L-Topological Spaces (European Journal of Pure and Applied Mathematics, 2025)
In this paper, we introduce and study the concept of nearly boundedness on arbitrary subsets in topological spaces which depended on the notion of   regular closed remoted neighborhood system. Several  characterizations of  nearly boundedness in terms of convergence theory of  filter, molecular nets and ideals are obtained. We prove that the concept is good extension, productive and topologically invariant.
Keywords: Molecules; regular closed remoted neighborhood; topological space; limit and cluster points; filter; molecular nets; ideals; Nearly compact and Nearly bounded sets